County-level neonatal opioid withdrawal syndrome rates and real-world access to buprenorphine during pregnancy: An audit (“secret shopper”) study in Missouri - Bronwyn S. Bedrick; Caroline Cary; Carly O'Donnell; Christine Marx; Hayley Friedman; Ebony B. Carter; Nandini Raghuraman; Molly J. Stout; Benson S. Ku; Kevin Y Xu; Jeannie C. Kelly (Drug and Alcohol Dependence Reports, 2024)
Background: Amid rising rates of neonatal opioid withdrawal syndrome (NOWS) worldwide and in many regions of the USA, we conducted an audit study (“secret shopper study”) to evaluate the influence of county-level buprenorphine capacity and rurality on county-level NOWS rates. Methods: In 2019, up to three phone calls were made to buprenorphine prescribers in the state of Missouri (USA). County-level buprenorphine capacity was defined as the number of clinicians (across all specialties) accepting pregnant people divided by the number of births. Multivariable negative binomial regression models estimated associations between buprenorphine capacity, rurality, and county-level NOWS rates, controlling for potential confounders (i.e., poverty, unemployment, and physician shortages) that may correspond to higher rates of NOWS and lower rates of buprenorphine prescribing. Analyses were stratified using tertiles of county-level overdose rates (top, middle, and lowest 1/3 of overdose rates). Results: Of 115 Missouri counties, 81(70 %) had no buprenorphine capacity, 17(15 %) were low-capacity (<0.5-clinicians/1,000 births), and 17(15 %) were high-capacity (≥0.5/1,000 births). The mean NOWS rate was 6.5/1,000 births. In Missouri counties with both the highest and lowest opioid overdose rates, higher buprenorphine capacity did not correspond to decreases in NOWS rates (incidence rate ratio[IRR]=1.23[95 %-confidence-interval[CI]=0.65–2.32] and IRR=1.57[1.21–2.03] respectively). Rurality did not correspond to greater NOWS burden in both Missouri counties with highest and lowest opioid overdose rates. Conclusions: The vast majority of counties in Missouri have no capacity for buprenorphine prescribing during pregnancy. Rurality and lower buprenorphine capacity did not significantly predict elevated rates of NOWS.